Retractions in Indian Business Research: A Closer Look at Trends, Reasons and Impacts of Retracted Articles - Basumatary, Bwsrang; Sinha, Manoj Kumar; Kumar, Vinit; Verma, Manoj Kumar (DESIDOC Journal of Library & Information Technology, 2025)
This study examines trends in retracted Indian business research articles from 2014 to 2023, focusing on various aspects such as the number of retractions, geographical distribution, associated journals and publishers, retraction timelines, reasons for retraction, and the citation impact before and after retraction. Using Scientometric tools, 79 retracted articles were analysed from the Retraction Watch and Scopus databases. The findings reveal a rising trend in retractions, predominantly due to fake peer reviews and plagiarism. Tamil Nadu recorded the highest number of retractions (n=44), with the “Journal of Ambient Intelligence and Humanized Computing” standing out with 17 retractions. Springer emerged as the leading publisher, accounting for 41 retractions. Most retractions occurred within a year of publication, and the articles continue to receive citations even after being retracted. The findings of this study will be beneficial for academic institutions, journal editors, and policymakers aiming to enhance research integrity and mitigate unethical practices in scholarly publishing.